Flexural testing of rectangular reinforced concrete beams with extruded plastic coarse aggregate replacement - Hicks, Cameron (Kansas State University, 2024)
Natural aggregates, used in reinforced concrete, are globally recognized as the most valuable non-fuel mineral commodity (Langer, 2002). As the global population continues to rise, the demand for concrete also increases, consequently elevating the need for aggregates. Natural aggregates such as sand, gravel, and crushed stone have passed the rate of renewal, and an aggregate replacement is necessary to meet the ever-increasing demand. Recycled plastic is a possible option for aggregate replacement in reinforced concrete. The utilization of recycled plastics serves the dual purpose of extracting plastic waste from the waste stream and partially replaces the need for natural aggregates. This research examines the effects of partial coarse aggregate replacement on reinforced concrete beams in four-point bending using a recycled plastic coarse aggregate called Plazrok by Enviroplaz. The reinforced concrete beams had a six-inch (152 mm) by 10-inch (254 mm) cross-section and a clear span of 12 feet (3,658 mm) between supports. Three mix designs were tested including a control, 15 percent, and 30 percent replacement by volume with Plazrok. Prior to the reinforced concrete beam tests, fresh (plastic state) and mechanical property tests such as density, slump, compression, tensile splitting, modulus of rupture, and reinforcement yield strength tests were conducted. Subsequently, the reinforced concrete beams were subjected to testing, and data on load-deflection were collected using an actuator and linear variable differential transformers (LVDT) along the beam. Crack propagation was monitored and documented throughout the tests. Utilizing the load-deflection data, various parameters including stiffness, modulus of elasticity (MOE), first crack, moment capacity at reinforcement yield, and ultimate strength were determined. Instantaneous deflection from experimental data was compared with deflection equations from mechanics of materials, specifically employing Bischoff's (2005) and Branson's (1965) effective moment of inertia equations. The objective was to confirm the validity of these equations for lightly reinforced concrete members with partial coarse aggregate replacement with Plazrok. Finally, the experimental flexural capacities were compared to nominal moment capacity equations developed based on the straight-line, parabolic stress, and equivalent stress theories. The results obtained from the reinforced concrete beam testing displayed promising results for partial coarse aggregate replacement for the 15 and 30 percent replacement members. At 15 and 30 percent replacement by volume there was no significant decrease in member capacity and underwent similar flexural behavior to the control members with a 6.9 and 28.5 percent increase in deflection at failure respectively. ACI 318-19 design method for flexural members was shown to be effective by underestimating the member strength up to 30 percent replacement. A 30 percent replacement was found to reduce stiffness and increase deflection significantly that would pose additional challenges in design.
Keywords: Concrete beam; Plastic aggregate; Sustainability; Mechanical properties; Flexural test; Coarse aggregate replacement